Metformin Ameliorates Gestational Diabetes Mellitus-Induced Endothelial Dysfunction via Downregulation of p65 and Upregulation of Nrf2 - Sun, Cong Cong; Lai, Ya Nan; Wang, Wen Huan; Xu, Xiao Min; Li, Xiao Qing; Wang, Hai; Zheng, Jia Yong; Zheng, Jian Qiong (Frontiers in Pharmacology, 2020)
Gestational diabetes mellitus (GDM) causes oxidative stress in mothers and infants and causes vascular endothelial dysfunction, which is a key factor for maternal and fetal cardiovascular diseases in the later stage of GDM, seriously threatening the life and health of mothers and infants. Nowadays, metformin (MET) has been discovered to improve endothelial function, but studies regarding the mechanism of MET improving endothelial cell function and alleviating endothelial function under hyperglycemia are still extremely limited. We aimed to investigate whether MET exerts its protective role against hyperglycemia-induced endothelial dysfunction through p65 and Nrf2. In our studies, applying cell migration assay and tube formation assay, we observed an obvious improvement of endothelial function under MET-treated, as characterized by that MET accelerated GDM-attenuated migration and angiogenesis of HUVECs. And ELISA assay results uncovered that Nrf2 expression level was decreased in GDM placenta, HVUECs and maternal serum comparing with normal group, however activation Nrf2 largely ameliorated tube formation under hyperglycemic condition. Furthermore, MET elevated the Nrf2 expression level and the level of nuclear Nrf2 accumulation in hyperglycemic HUVECs. Besides, preliminary evidence predicted that Nrf2 expression was modulated by transcription factor p65, which was increased in GDM peripheral blood, placenta and HUVECs, and suppression of p65 could recover GDM-induced suppression of angiogenesis. In addition, we also confirmed MET restores the GDM-induced angiogenesis impairment may via downregulation of p65 and upregulation of Nrf2. Taken together, the endothelial protective effect of MET under GDM (HG) conditions could be partly attributed to its role in downregulating p65 and upregulating Nrf2.